STRATEGI GURU DALAM MENGATASI KESULITAN MEMBACA PADA SISWA KELAS 1 SEKOLAH DASAR NEGERI 25 BANDA ACEH - Niswatun Nafis; Teuku Mahmud; Hendra Kasmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading is a fundamental skill that is crucial for elementary school students, especially in the early grades. However, many first-grade students experience reading difficulties, such as difficulty recognizing letters, spelling, pronouncing words, and understanding the content of the reading. These difficulties can impact the overall learning process and outcomes. Therefore, the role of teachers is crucial in implementing appropriate learning strategies to help students overcome reading difficulties. This study aims to determine teachers' strategies for overcoming reading difficulties in first-grade students at SD Negeri 25 Banda Aceh. This study used a qualitative approach with a descriptive research type. The subjects were first-grade teachers, while the objects of the study were the strategies used by teachers to overcome students' reading difficulties. Data collection techniques were carried out through observation, interviews, and documentation. The results showed that teachers implemented several strategies to overcome reading difficulties, including the use of learning-based games such as letter cards, the use of visual media in the form of picture books and vocabulary books, providing positive feedback in the form of praise and motivation, and collaboration with parents to support students' reading activities at home. These strategies were considered quite helpful in gradually improving students' reading abilities, although special assistance is still needed for students who experience certain difficulties. Thus, it can be concluded that the application of appropriate and varied learning strategies by teachers plays a very important role in helping to overcome reading difficulties in first grade students.